A computational fluid dynamics analysis of the wave soldering process. Issue 5 (1st June 2015) - Abdul Aziz, M.S.; Abdullah, M.Z.; Khor, C.Y.; Mazlan, M.; Iqbal, A.M.; Fairuz, Z.M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a three-dimensional finite volume-based analysis on the effects of propeller blades on fountain flow in a wave soldering process and performs an experimental validation. Design/methodology/approach – Solder pot models with various numbers of propeller blades were developed and meshed by using hybrid elements and simulated by using the FLUENT fluid flow solver. The characteristics of the fountain, such as flow profile, velocity vector, filling time, and fountain advancement, were investigated. Molten solder (Sn63Pb37) material, a temperature of 250°C, and a propeller speed of 830 rpm were applied in the simulation. The predicted results were validated by the experimental fountain profile. Findings – The use of a six-blade propeller in a solder pot increased the fountain thickness profile and reduced the filling time. Moreover, a six-blade propeller design resulted in a stable fountain profile and was considered the best choice for current wave soldering processes. Practical implications – This study provides a better understanding of the effects of propeller blades on the fountain flow in the wave soldering process. Originality/value – The study explores the fountain flow behavior and provides a reference to the engineers and designers in order to improve the fountain flow of the wave soldering.